Palatability and Mortality of Japanese Quails Fed Diets Supplemented with Black Soldier Fly Larvae Meal - Abdul Mukhlis Alhanif; Supranoto Supranoto; Tri Sukmaningsih; Wida Nurnaningsih (MEDIA PETERNAKAN, 2026)
This study evaluated the effects of dietary black soldier fly (BSF; Hermetia illucens) larvae meal supplementation on feed palatability and mortality of female Japanese quails (Coturnix japonica) during the grower-to-layer transition. The experiment used a completely randomized design with four treatments: P0 (basal diet without BSF meal), P1 (basal diet + 8% BSF meal), P2 (basal diet + 16% BSF meal), and P3 (basal diet + 24% BSF meal), each replicated five times with six birds per replicate (n = 120). Palatability was measured as feed consumed during the first hour after feeding, recorded separately for grower (21–42 days) and layer (43–63 days) phases. Mortality was calculated as the percentage of dead birds relative to the initial number per experimental unit throughout the study. Data were analyzed using one-way ANOVA followed by least significant difference (LSD) tests. BSF meal supplementation significantly reduced palatability during the grower phase (P < 0.01), decreasing from 4.06 g in P0 to 3.10 g, 2.98 g, and 3.01 g in P1, P2, and P3, respectively, with no significant differences among the BSF-supplemented groups. In the layer phase, palatability was unaffected (P > 0.05), ranging from 7.63 to 7.78 g. Mortality remained low (0–3.33%) and did not differ significantly among treatments in either phase (P > 0.05). These findings indicate that BSF meal can be included up to 24% in quail diets without increasing mortality, but high inclusion may temporarily depress early feed acceptance during the grower phase. Gradual adaptation and lower initial inclusion are recommended to optimize feed palatability.